Analytical investigation of outflow currents in applied field magnetoplasmadynamic thrusters. (February 2023) - Wu, Peng; Wang, Yibai; Li, Yong; Zhou, Cheng; Wang, Yimeng; Chen, Zhiyuan; Han, Xing; Tang, Haibin
Abstract: An applied field magnetoplasmadynamic thruster (AF-MPDT) is one of the most promising electric engines for the space missions with high thrust. However, the acceleration mechanisms in AF-MPDTs are complicated because of the application of the magnetic nozzle, which limits the performance improvement of the thrusters. The discharge currents may flow out of the discharge chamber because of the magnetic nozzle, which was neglected in previous research studies about the acceleration mechanisms in AF-MPDTs. A model based on the MHD equations has been established to investigate the contribution of outflow currents to the plasma acceleration. The accuracy of the model has been proved by the comparison of the calculated thrust and the experimental data. The performance of the argon-fed AF-MPDT is measured by a target thrust stand. The dominant acceleration mechanism of the AF-MPDTs is the plasma expansion in the magnetic nozzle when the magnetic fields are less than 0.2 T. The primary thermal energy source of the AF-MPDTs is the Joule heating when the magnetic fields are lower than 0.1 T. The viscous heating due to the outflow currents will be dominant when the magnetic fields are higher. An AF-MPDT without a discharge chamber is proposed to improve the performance. Compared with the conventional AF-MPDT, the new structure may provide an average 15% increase in performance at the same condition. Graphical abstract: Highlights: The influences of outflow currents on plasma acceleration are studied. Higher outflow currents are beneficial for plasma acceleration in AF-MPDTs. The plasma expansion is the dominant acceleration mechanism in AF-MPDTs. An AF-MPDT without a discharge chamber is proposed for performance improvement.